Informing NHS policy in 'digital-first primary care': a rapid evidence synthesis - Mark Rodgers; Gary Raine; Sian Thomas; Melissa Harden; Alison Eastwood (National Institute for Health Research, 2019)
Background: In 'digital-first primary care' models of health-care delivery, a patient's first point of contact with a general practitioner or other health professional is through a digital channel, rather than a face-to-face consultation. Patients are able to access advice and treatment remotely from their home or workplace via a number of different technologies. Objectives: This rapid responsive evidence synthesis was undertaken to inform NHS England policy in 'digital-first primary care'. It was conducted in two stages: (1) scoping the published evidence and (2) addressing a refined set of questions produced by NHS England from the evidence retrieved during the scoping stage. Data sources: Searches were conducted of five electronic databases (MEDLINE, Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effects, the Health Technology Assessment database and PROSPERO were searched in July 2018) and relevant research/policy and government websites, as well as the National Institute for Health Research Health Service and Delivery Research programme database of ongoing and completed projects. No date or geographical limitations were applied. Review methods: After examining the initial scoping material, NHS England provided a list of questions relating to the potential effects of digital modes and models of engagement, and the contracting and integration of these models into primary care. Systematic reviews and evidence syntheses, including evidence on the use of digital (online) modes and models of engagement between patients and primary care, were examined more closely, as was ongoing research and any incidentally identified primary studies focused on the use of digital (online) modes and models of engagement. All records were screened by two reviewers, with disagreements resolved by consensus or consulting a third reviewer. Results: Evidence suggests that uptake of existing digital modes of engagement is currently low. Patients who use digital alternatives to face-to-face consultations are likely to be younger, female and have higher income and education levels. There is some evidence that online triage tools can divert demand away from primary care, but results vary between interventions and outcome measures. A number of potential barriers exist to using digital alternatives to face-to-face consultations, including inadequate NHS technology and staff concerns about workload and confidentiality. There are currently insufficient empirical data to either substantiate or allay such concerns. Very little evidence exists on outcomes related to quality of care, service delivery, benefits or harms for patients, or on financial costs/cost-effectiveness. No studies examining how to contract and commission alternatives to face-to-face consultations were identified. Limitations: The quality of the included reviews was variable. Poor reporting of methodology and a lack of adequate study details were common issues. Much of the evidence focused on exploring stakeholder views rather than on objective measurement of potential impacts. The current evidence synthesis is based on a rapid scoping exercise and cannot provide the breadth or depth of insight that might have been achieved with a full systematic review. Conclusions: Rapid scoping of the literature suggests that there is little high-quality evidence relating to 'digital-first primary care' as defined by NHS England. The broader evidence on alternatives to face-to-face consultation addresses certain policy-maker concerns, such as the possible impact of new technologies on workload and workforce, inequalities, local implementation and integration with existing services. However, although this evidence gives an insight into the views and experiences of health professionals in relation to such concerns, quantitative empirical data are lacking. Funding: The National Institute for Health Research Health Service and Delivery Research programme.